Therapeutic response differences between 2D and 3D tumor models of magnetic hyperthermia. Issue 13 (1st June 2021) - Gupta, Ruby; Sharma, Deepika
Abstract : 3D hyperthermia models exhibit potential for successful translation to clinical applications as greater heat stress response is generated in cells cultured in 3D as spheroids, inserts, scaffolds and microfluidic chips than cultured as monolayers. Abstract : Magnetic hyperthermia-based cancer therapy (MHCT) has surfaced as one of the promising techniques for inaccessible solid tumors. It involves generation of localized heat in the tumor tissues on application of an alternating magnetic field in the presence of magnetic nanoparticles (MNPs). Unfortunately, lack of precise temperature and adequate MNP distribution at the tumor site under in vivo conditions has limited its application in the biomedical field. Evaluation of in vitro tumor models is an alternative for in vivo models. However, generally used in vitro two-dimensional (2D) models cannot mimic all the characteristics of a patient's tumor and hence, fail to establish or address the experimental variables and concerns. Considering that three-dimensional (3D) models have emerged as the best possible state to replicate the in vivo conditions successfully in the laboratory for most cell types, it is possible to conduct MHCT studies with higher clinical relevance for the analysis of the selection of magnetic parameters, MNP distribution, heat dissipation, action and acquired thermotolerance in cancer cells. In this review, various forms of 3D cultures have been considered and the successful implication of MHCT on them has been summarized, which includes tumor spheroids, and cultures grown in scaffolds, cell culture inserts and microfluidic devices. This review aims to summarize the contrast between 2D and 3D in vitro tumor models for pre-clinical MHCT studies. Furthermore, we have collated and discussed the usefulness, suitability, pros and cons of these tumor models. Even though numerous cell culture models have been established, further investigations on the new pre-clinical models and selection of best fit model for successful MHCT applications are still necessary to confer a better understanding for researchers.